2016
DOI: 10.1038/bmt.2016.255
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory research for optimal GvHD prophylaxis after single unit CBT in adults: short-term methotrexate reduced the incidence of severe GvHD more than mycophenolate mofetil

Abstract: In order to examine GvHD prophylaxis in umbilical cord blood transplantation (UCBT) in more detail, we compared transplant outcomes after UCBT for acute leukemia among GvHD prophylaxes using registry data. We selected patients transplanted with a calcineurin inhibitor and methotrexate (MTX)/mycophenolate mofetil (MMF) combination. A total of 1516 first myeloablative UCBT between 2000 and 2012 (Cyclosporine A (CyA) plus MTX, 824, Tacrolimus (Tac) plus MTX, 554, Tac plus MMF, 138) were included. With adjusted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 51 publications
3
13
0
3
Order By: Relevance
“…The significant association between increased CRP levels and decreased 16-hour CCI may be explained by the frequent occurrence of PES after CBT. In addition, GVHD prophylaxis using methotrexate may contribute to better platelet transfusion responses found in our study, probably because using methotrexate for GVHD prophylaxis has been reported to reduce the incidence of PES and acute GVHD after CBT [28][29][30]. These findings suggested that development of PES may be strongly associated with PTR after CBT.…”
Section: Discussionsupporting
confidence: 54%
“…The significant association between increased CRP levels and decreased 16-hour CCI may be explained by the frequent occurrence of PES after CBT. In addition, GVHD prophylaxis using methotrexate may contribute to better platelet transfusion responses found in our study, probably because using methotrexate for GVHD prophylaxis has been reported to reduce the incidence of PES and acute GVHD after CBT [28][29][30]. These findings suggested that development of PES may be strongly associated with PTR after CBT.…”
Section: Discussionsupporting
confidence: 54%
“…These results are better than previous studies of i.v. CBT for adult patients, but they may be inconsistent with animal experiments showing that intrabone transplantation is 10–15 times more efficient in the engraftment of cord blood cells than i.v. transplantation .…”
Section: Discussionmentioning
confidence: 97%
“…The median time to neutrophil recovery was 17–23 days, and platelet recovery was 32–41 days, which are much faster than i.v. CBT . A retrospective comparative study showed that neutrophil recovery was significantly faster in intrabone single CBT than in i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fludarabine plus busulfan might be preferable in patients who receive Moga before allo‐HSCT. In terms of GVHD prophylaxis in the setting of CBT, TAC plus MTX was associated with a lower incidence of GVHD than TAC plus mycophenolate mofetil . Thus, TAC plus MTX might be preferable in patients who receive Moga before allo‐HSCT.…”
Section: Key Scientific Statement To the Clinical Questions Regardingmentioning
confidence: 99%